Correlations of Prompt and Afterglow Emission in Swift Long and Short Gamma-Ray Bursts - Gehrels, N; Barthelmy, S. D; Burrows, D. N; Cannizzo, J. K; Chincarini, G; Fenimore, E; Kouveliotou, C; O’Brien, P; Palmer, D. M; Racusin, J; Roming, P. W. A; Sakamoto, T; et al. (The Astrophysical journal, 2008)
Correlation studies of prompt and afterglow emission from gamma-ray bursts (GRBs) between different spectral bands have been difficult to do in the past because few bursts had comprehensive and comparable afterglow measurements. In this paper we present a large and uniform data set for correlation analysis based on bursts detected by the Swift mission. For the first time, short and long bursts can be analyzed and compared. It is found for both classes that the optical, X-ray, and gamma-ray emission are linearly correlated, but with a large spread about the correlation line; stronger bursts tend to have brighter afterglow, and bursts with brighter X- ray afterglow tend to have brighter optical afterglow. Short bursts are, on average, weaker in both prompt and afterglow emission. No short bursts are seen with extremely low optical-to-X-ray ratios, as occurs for "dark" long bursts. Although statistics are still poor for short bursts, there is no evidence yet for a subgroup of short bursts with high extinction, as there is for long bursts. Long bursts are detected in the dark category in the same fraction as pre-Swift bursts. Interesting cases of long bursts that are detected in the optical, and yet have a low enough optical-to-X-ray ratio to be classified as dark, are discovered. For the prompt emission, short and long bursts have different average tracks on flux versus fluence plots. In Swift, GRB detections tend to be fluence-limited for short bursts and flux-limited for long events.